The role of IL-17 family cytokines in cardiac fibrosis - Huang, Liqing (Frontiers in Cardiovascular Medicine, 2024)
Myocardial fibrosis is a common pathological feature in various cardiovascular diseases including myocardial infarction, heart failure, and myocarditis. Generally, persistent myocardial fibrosis correlates with poor prognosis and ranks among the leading causes of death globally. Currently, there is no effective treatment for myocardial fibrosis, partly due to its unclear pathogenic mechanism. Increasing studies have shown IL-17 family cytokines are strongly associated with the initiation and propagation of myocardial fibrosis. This review summarizes the expression, action, and signal transduction mechanisms of IL-17, focusing on its role in fibrosis associated with cardiovascular diseases such as myocardial infarction, heart failure, hypertension, diabetes, and myocarditis. It also discusses its potential as a therapeutic target, offering new insights for the clinical treatment of myocardial fibrosis.